1993
DOI: 10.1136/thx.48.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Value of theophylline treatment in patients handicapped by chronic obstructive lung disease.

Abstract: Background It is still not certain whether it is worth using theophylline in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
9

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 36 publications
0
34
0
9
Order By: Relevance
“…Combining these drugs produces the following additional benefits. In general, oral theophylline is a weakly effective bronchodilator and has more side-effects at pharmacological doses [34]. Inhaled corticosteroids produce a small improvement in post-bronchodilator FEV1 comparable with that due to longacting b-agonists (LABA) in some [35], but not all [36], clinical studies.…”
Section: Drugs and The Secondary Prevention Of Copdmentioning
confidence: 99%
“…Combining these drugs produces the following additional benefits. In general, oral theophylline is a weakly effective bronchodilator and has more side-effects at pharmacological doses [34]. Inhaled corticosteroids produce a small improvement in post-bronchodilator FEV1 comparable with that due to longacting b-agonists (LABA) in some [35], but not all [36], clinical studies.…”
Section: Drugs and The Secondary Prevention Of Copdmentioning
confidence: 99%
“…Mode of administration, chemical structure, log , and 1/2 values of anticholinergics are given in Table 2. [33]. For example, changes in respiratory muscle function have been reported in patients treated with theophylline [34], but whether this reflects changes in dynamic lung volumes or a primary effect on the muscle remains unclear.…”
Section: Anticholinergicsmentioning
confidence: 99%
“…Theophylline has been shown to non-selectively inhibit several PDE isoforms in the airways 60 . Randomized controlled studies have shown that theophylline alone or in addition to bronchodilators and corticosteroids improves respiratory function, dyspnoea and exercise tolerance in patients with severe COPD 61,62 .…”
Section: Theophyllinementioning
confidence: 99%